شهده الكاتبة (ت 574 ﮬ ) قراءة في سيرتها وجهودها في العلوم الدينية - مهدي, م. نجلاء كريم; الشريفي, م. بيداء محمد (مجلة دراسات في التاريخ والآثار, 2020)
الملخص:-          تناول البحث دراسة الفقيهة الكاتبة شهده , إحدى عالمات بغداد , والتي عاصرت الخلفاء العباسيين ومنهم الخليفة المقتفي لأمر الله , وكانت هي وزوجها من خواصه , تتلمذت على يد أكابر الفقهاء في بغداد , ومنهم أبيها احمد بن الفرج , لم ينحصر اهتمامها برواية الحديث فقط إنما اجتهدت بتفسير بعضا من آيات الذكر الحكيم  , فضلا عن إلمامها بالمسائل الفقهية .Abstract:-           The study dealt with the fiction of the writer witnessed, one of the signs of Baghdad, and the Abbasid Caliphs, including the successor to the order of God, and she and her husband of his characteristics, studied by the most prominent jurists in Baghdad, including her father Ahmed bin al-Faraj, Some of the verses of al-Hakim, as well as their knowledge of matters of jurisprudenc